Study on structural modeling and kinematics analysis of a novel wheel-legged rescue robot. (12th January 2018) - Niu, Jianye; Wang, Hongbo; Shi, Hongmin; Pop, Nicolae; Li, Dong; Li, Shanshan; Wu, Shaozhen
This article presents a novel rescue robot with three-degrees of freedom leg mechanism based on the serial–parallel and wheel-legged mechanisms, which consists of two U niversal joint- P rismatic joint- S pherical joint plus one U niversal joint and R evolute joint serial–parallel mechanism. Firstly, the structure model of the whole mechanism and the leg mechanism is developed, the dimension parameters of leg mechanism are designed, and the degrees of freedom of the whole mechanism and the leg mechanism is analyzed. Secondly, the forward and backward position solutions of the swing leg and the standing leg are solved, and the work space is obtained. Thirdly, the kinematics is investigated by the influence coefficient method, including the Jacobi matrix and linear velocity and angular velocity of each rod's centroid of the leg mechanism. Finally, the simulation and experiment are carried out, and the feasibility of this wheel-legged rescue robot and the correctness of the above research are verified.